Seroprevalence of Dengue IgG Antibodies among Healthy Adult Population in Lahore, Pakistan. (12th September 2013) - Mahmood, Shahid; Nabeel, Hiba; Hafeez, Saadia; Zahra, Urooj; Nazeer, Hammad
Abstract : Background . Dengue is a mosquito-borne flavivirus infection prevalent in tropical and subtropical regions around the world. Aim of this study was to determine seroprevalence of anti-dengue IgG antibodies in healthy adult population of Lahore and also describe risk factors in relation to dengue seropositivity. Methods . In this cross-sectional study, 274 healthy adult individuals aged 15 years and above were randomly selected using multistage sampling technique. These individuals were interviewed between July–September 2012, using a semistructured questionnaire, followed by drawing 3 mL of their venous blood for dengue IgG test. Nova Tech ELISA kit with sensitivity and specificity of 96.5% and 97.5%, respectively, was used for serology. Results . Out of 274 participants, 184 (67.2%) were found to be positive for dengue IgG antibodies. Seroprevalence was higher among individuals with poor awareness about potential breeding sites for dengue mosquito (63.6%), followed by the subjects who had poor knowledge about dengue signs/symptoms and complications (52.2% and 68.5%, resp.). Conclusion . About two-third of healthy population of Lahore was also seropositive for anti-dengue IgG during July–September 2012, indicating a considerable burden of subclinical dengue infection in the city. Males were predominantly affected than the females. We found no statistical association between dengue IgG seropositivity and socioeconomic status, occupation, and knowledge about the disease.